Optimization and Characterization of Fenofibrate Self-Nanoemulsifying Drug Delivery System (SNEDDS) Preparations - Sukarno; Ilham Kuncahyo; Endang Dyah Ikasari (Open Access Indonesian Journal of Medical Reviews, 2024)
Fenofibrate is a third-generation fibric acid derivative included in BCS (biopharmaceutical classification system) class II, namely high permeability, low solubility. This research aims to obtain the optimum formula for miglyol oil, cremophor RH 40 and PEG 400 according to characterization tests of emulsification time, % transmittance, drug loading, globule size, and zeta potential. This research is an experimental study by formulating fenofibrate in the form of SNEDDS, which was made in 16 formulas using the D-optimal method, which was formulated in the form of SNEDDS with the composition miglyol, cremophor RH 40 and PEG 400 and characterization tests were carried out for emulsification time, % transmittance, drug loading, size. globules, zeta potential to obtain the optimum formula, and then analyzed using the one sample T-Test. The optimization results obtained the optimum formula, namely miglyol at 4%; cremophor RH 40 is 5%, and PEG 400 at 1%. Characterization test: emulsification time was 24 seconds, Transmittance % was 98.7%, Drug loading was 181 mg, globule size was 126 nm, and zeta potential of 12.26 mV. The dissolution test of the fenofibrate capsule dissolved 57.05%, while the fenofibrate SNEDDS capsule was 64.86%. This means that the dissolution of the optimum formula for SNEDDS fenofibrate is better than pure fenofibrate.